Penerapan Model Pembelajaran Means-Ends Analysis Dalam Meningkatkan Pemahaman Siswa Pada Proses Pembelajaran Ekonomi Di Kelas XI SMAN 15 Muaro Jambi - Ferdiyansyah, Firman; Kasiono, Kasiono (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the application of conventional learning models in improving class XI students' understanding of economics subjects at SMAN 15 Muaro Jambi. The research design that will be carried out in this research is quasi-experimental research with a quantitative approach. The research results show that the application of the Means-Ends Analysis (MEA) learning model has proven effective in improving student learning outcomes in many aspects such as knowledge and skills. This is because MEA is hands-on and builds enthusiasm for learning so that the learning process can be student-centered rather than the role of the teacher